Genome-wide identification and expression analysis of ARF gene family in embryonic development of Korean pine (Pinus koraiensis) - Yue Zhang; Wei Wu; Hailong Shen; Ling Yang (BMC Plant Biology, 2024)
Abstract Background The Auxin Responsive Factor (ARF) family plays a crucial role in mediating auxin signal transduction and is vital for plant growth and development. However, the function of ARF genes in Korean pine (Pinus koraiensis), a conifer species of significant economic value, remains unclear. Results This study utilized the whole genome of Korean pine to conduct bioinformatics analysis, resulting in the identification of 13 ARF genes. A phylogenetic analysis revealed that these 13 PkorARF genes can be classified into 4 subfamilies, indicating the presence of conserved structural characteristics within each subfamily. Protein interaction prediction indicated that Pkor01G00962.1 and Pkor07G00704.1 may have a significant role in regulating plant growth and development as core components of the PkorARFs family. Additionally, the analysis of RNA-seq and RT-qPCR expression patterns suggested that PkorARF genes play a crucial role in the development process of Korean pine. Conclusion Pkor01G00962.1 and Pkor07G00704.1, which are core genes of the PkorARFs family, play a potentially crucial role in regulating the fertilization and developmental process of Korean pine. This study provides a valuable reference for investigating the molecular mechanism of embryonic development in Korean pine and establishes a foundation for cultivating high-quality Korean pine.